Legal protection for Provider in Peer to Peer Lending: an Example from Indonesian Regulation - Trinas Dewi Hariyana (Indonesian Journal of Law and Economics Review, 2019)
The Financial Technology peer to peer (P2P) lending concept still finds many weaknesses, especially in terms of legal protection for parties and risk management from Fintech itself. P2P Lending Regulation in Indonesia currently uses POJK No. 77 / POJK / 2016 concerning technology-based money lending and borrowing services. The position of Fintech P2P lending is similar to a bank, but the concept is a different agreement. Fintech P2P lending funds can come from investors or funders or cooperate with legal entities or banks. Considering that the risk posed by Fintech P2P lending is very large, Fintech must also implement consumer protection, risk management and prudential principles like a bank credit agreement so as to cover the risk of bad credit, the Fintech platform uses other means to protect funds from investors or investors. the other is with the protection fund as done by the Coin works platform. The protection fund does not cover the entire fund invested by the funder, depending on the availability of protection funds and the amount of credit that is experiencing congestion. The POJK regulation in article 19 describes the agreement clause which must contain the dispute resolution mechanism and the settlement mechanism if the implementation of lending and borrowing services is not able to continue operations, so that with the rules related to the clause it is expected that the funder will still get legal certainty and protection for funds.